2007
DOI: 10.1177/1077558707309613
|View full text |Cite
|
Sign up to set email alerts
|

Review: How Do Hospital Organizational Structure and Processes Affect Quality of Care?

Abstract: Interest in organizational contributions to the delivery of care has risen significantly in recent years. A challenge facing researchers, practitioners, and policy makers is identifying ways to improve care by improving the organizations that provide this care, given the complexity of health care organizations and the role organizations play in influencing systems of care. This article reviews the literature on the relationship between the structural characteristics and organizational processes of hospitals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 100 publications
1
116
0
3
Order By: Relevance
“…The study showed that the largest network of obstetric and neonatal care is outsourced by the SUS, corroborating similar studies in Rio de Janeiro 3,7 , Greater Metropolitan São Paulo 22 , and Santa Catarina State 27 .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The study showed that the largest network of obstetric and neonatal care is outsourced by the SUS, corroborating similar studies in Rio de Janeiro 3,7 , Greater Metropolitan São Paulo 22 , and Santa Catarina State 27 .…”
Section: Discussionsupporting
confidence: 75%
“…To measure quality of healthcare, Donabedian 6 proposed a theoretical framework based on structure, process, and outcomes, a triad that has been widely used in health services research 7 . Structure refers to the relatively stable characteristics of services, including the availability of human and financial resources, equipment, and inputs, in addition to their organizational format.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29] Authentic transformational leadership is the backbone of high-performing and highly effective health care systems, as evidenced through quality of care, patient satisfaction, workforce satisfaction, organizational effectiveness, performance and social responsibility. [30,31] Authentic transformational leadership engages and motivates professionals to collaborate in integrating their work horizontally and vertically in emergency management systems. This leadership is also necessary in bringing about transformational changes within integrated health care delivery systems accountable for the overall positive outcomes that include lower mortality and morbidity rates.…”
Section: Theoretical Framework: a Triangulation Approachmentioning
confidence: 99%
“…However, each public hospital has the ability and creativity to maintain quality in services and activities based on their own strategic management and governance as a Local General Services Body. As previos studies show inconsistent results between regulatory processes and quality outcomes [11] and lack on pratices and processes of quality improvement due to limited human resources and lack of competent staff [12]. Thus, the aim of this study is to understand the cycle of data collecting and reporting processes on performance measurement data in public hospitals.there are such policies supporting for quality improvement.…”
Section: Introductionmentioning
confidence: 99%